Analysis of Toddler Fundamental Movement on Development of Kinesthetic Intelligence. - Solahudin Anwar, Aang; Prihamdani, Depi; Oktaviani, Desy (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the analysis of basic motor movements of gross and fine motoric children under five (ages 3-5 years) on the development of kinesthetic intelligence and find out the extent of the results of increased kinesthetic intelligence of children through fundamental movements (walking, running and jumping) One of the intelligence of intelligence compound is kinesthetic intelligence, this becomes a determining factor for a child in supporting its growth and development. Kinesthetic intelligence can also support other anxiety so that it supports the success of children in the future. Research methods conducted using qualitative research methods. By analyzing a number of toddlers in the indo natural residential environment. The results showed an analysis that children who have fundamental movements (basic movements of walking, running and jumping) are directly proportional to the kinesthetic intelligence of children under five years old.